Geochemistry And Petrography Characterization Of Ordovician Devonian Limestone Formation In Kinta District, Perak - Zahisham, Zahira Sofiya (Universiti Sains Malaysia, 2022)
Limestone are one of the foremost vita of all sedimentary rock. It is composed largely of calcium carbonate (CaCO3) within the mineral form calcite or aragonite, and there are a few other imperative carbonate minerals with which limestones are related. It may contain considerable amount of magnesium carbonate (dolomite) as well as minor constituents moreover commonly display incorporate clay, feldspar, quartz, pyrite, and iron carbonate. The main obejective of this project is to evaluate the chemical composition and petrography properties of the carbonate sample, to determine the dissolution performance of the carbonate sample, and to correlate mineralogy, chemical composition and dissolution performance to karstification features, and also durability of of the carbonate sample. The carbonate sample from quarry and limestone outcrop in Kinta Valley will be taken to undergo petrographic and geochemical analysis. X-Ray Diffraction (XRD) were used for the mineral characterization of the samples. The analysis of petrographic thin section is performed by examining thin section under a polarizing microscope to observe the mineralogical features and textural variations in order to determine their petrographic characteristics. Besides that, dissolution test and slake durability were also conducted as it related to karstification and weathering respectively. Calcite is abundant in carbonate rocks from selected quarries whereas other minerals are few. Different mineral concentrations and compositions can help explain the unique features of each carbonate rock such as color, strength, and moisture content. Understanding secondary process like karstification, dolomization, and dissolution can be aided by complete petrographic and geochemical study of carbonate rocks in Kinta Valley . From all the results, the correlation between mineralogy, chemical and mechanical properties of the rock were made. Most of the sample has high durability index. This can be approve from dissolution performance of the sample. Limestone rock from selected area in Kinta Valley have high content of calcite with low content of other minerals. Minerals and their properties that are invisible to the human eye can be observed on photomicrograph, and the existence of the mineral was confirmed by XRD analyses while the durability of the rock related to weathering can be known from the mechanical test conducted.